Clinical diagnosis of stroke patients using SIRIRAJ stroke score and Computed Tomography - Ram Narayan Mandal,; Ajay Kumar Mishra,; Elena Leonidovna Mandal,; Margarita Ramovna Mandal,; Shambhu Sah,; Vijay Kumar Sah,; Rajiv Jha, (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Stroke is a significant cause of disability and death globally, with ischemic and hemorrhagic types. Rapid diagnosis is critical, particularly in resource-limited settings where access to neuroimaging is restricted. Thus, this study aimed to diagnose stroke patients using the Siriraj Stroke Score (SSS) and computed tomography at Janaki Medical College Teaching Hospital. Materials and Methods: A total of 97 stroke patients presented within 72 hours of onset at Janaki Medical College Teaching Hospital, Nepal, were included in this study. Patients were clinically assessed using the SSS and subsequently underwent CT brain scanning to confirm the stroke subtype. The SSS was calculated based on consciousness level, headache, vomiting, atheroma markers, and diastolic blood pressure. The results from SSS were compared with the CT scan findings to determine the clinical diagnosis. Results: The study found that 56.7% of the patients had hemorrhagic strokes, with intraparenchymal hematoma being the most common subtype. The SSS showed a strong correlation with CT scan results, particularly for hemorrhagic strokes, where most patients with a score above 1 were accurately diagnosed. Conclusion: The Siriraj Stroke Score is a valuable tool for initial stroke assessment, especially in settings where advanced neuroimaging is not immediately available. The study supports using SSS in early stroke management, which could improve patient outcomes in resource-limited environments.